Eye movement abnormalities in Alzheimer’s disease and other neurodegenerative dementias: insights from current evidence and priorities for future research - Anagnostou, Evangelos; Armenis, Georgios (Frontiers in Ophthalmology, 2025)
Eye movement abnormalities are increasingly recognized as early and sensitive markers of neurodegenerative dementias, particularly Alzheimer’s disease (AD). Disruptions in saccadic, antisaccadic, smooth pursuit, fixation, and naturalistic eye movement tasks reflect dysfunction in frontal, parietal, subcortical, and cerebellar circuits that are vulnerable to neurodegeneration. Studies have consistently demonstrated that AD patients show prolonged saccadic latencies, increased antisaccade error rates, reduced smooth pursuit gain, and fixation instability. Such deficits correlate with cognitive impairment, disease severity, and neuroimaging biomarkers of cortical atrophy. Comparisons with frontotemporal dementia (FTD), dementia with Lewy bodies (DLB), and posterior cortical atrophy (PCA) highlight overlapping yet distinct oculomotor profiles, suggesting diagnostic and prognostic value. Eye-tracking methodologies offer non-invasive, cost-effective tools that could complement neuropsychological and imaging assessments. However, methodological variability remains a barrier to clinical implementation. This review integrates evidence from foundational and recent studies to provide a comprehensive account of oculomotor dysfunction in AD and other dementias, emphasizing the translational potential of eye movement biomarkers in clinical practice and research.